Analysis of Factors Influencing Taxpayer Compliance in Paying Land and Building Tax with Islamic Faith - Nur Risqiananda; Della Fadhilatunisa; Raodahtul Jannah (Journal of Applied Taxation and Policy, 2025)
This study examines the influence of tax knowledge, tax sanctions, and tax awareness on taxpayer compliance in paying land and building tax (PBB), with Islamic faith as a moderating variable. The research addresses the issue of fluctuating PBB revenue in Bone Regency and the need to understand behavioral and spiritual factors underlying tax compliance. The study used a quantitative approach with purposive sampling of 100 individual taxpayers in Tanete Riattang Barat District, Bone Regency. Data were collected through questionnaires and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that tax knowledge, tax sanctions, and tax awareness significantly and positively affect taxpayer compliance. Further, Islamic faith moderates the effect of tax sanctions on compliance, but does not moderate the relationship between tax knowledge or tax awareness and compliance. These findings highlight that while knowledge and awareness are important determinants of compliance, religiosity is more influential in reinforcing the deterrent effect of sanctions rather than enhancing knowledge or awareness. This study contributes to the literature by integrating Islamic values into tax compliance analysis, an area rarely explored in previous research. Practically, the results suggest that local governments should strengthen education and awareness programs while considering cultural and religious aspects in tax policy design.